Never fall again - Blackburn, Lynn Huggins (Gossamer Falls, 2024)
"Landry Hutton, quiet artist-in-residence of The Haven, came to Gossamer Falls to build a new life and a new home for her and her daughter--with the unexpected help of a handsome former Marine. But when danger threatens them, can Callum Shaw help protect both their hearts and lives?"--